Assessing the impact of Queensland's late‐night alcohol restrictions using health system data. (19th May 2021) - Livingston, Michael; Coomber, Kerri; de Andrade, Dominique; Taylor, Nicholas; Ferris, Jason; Puljević, Cheneal; Miller, Peter G.
Abstract: Introduction and Aims: In an attempt to reduce alcohol‐related harm in night‐time entertainment precincts, the Queensland state government (Australia) introduced the Tackling Alcohol‐Fuelled Violence strategy in July 2016, including restrictions on late‐night service of alcohol and—later—compulsory ID scanners at venues. In this article, we examined the impact of these changes on emergency department (ED) presentations and hospital admissions for alcohol‐related harm. Design and Methods: We used data on ED presentations (July 2009–June 2019) and hospital admissions (July 2009–December 2018). Interrupted time series models using seasonal auto‐regressive integrated moving average methods were developed to test the impact of the policy change on presentations for alcohol intoxication, any injury or maxillofacial fractures, and admissions for rates of assault‐related injuries or maxillofacial fractures. Analyses were conducted using state‐wide Queensland data with a sub‐analysis focussing on major Brisbane hospitals. Results: The introduction of 3 am last drinks and mandatory ID scanners had no significant impact on most outcome measures, either across the state or within Brisbane. State‐wide, there was a significant decline in ED injury presentations following the introduction of mandatory ID scanners. Discussion and Conclusions: The introduction of the Tackling Alcohol‐Fuelled Violence strategy in Queensland Safe Night Precincts was potentially associated with a small reduction in injury presentations to EDs. The lack of other impacts may relate to the relative lack of specificity in health system data, which challenges in the implementation of the Tackling Alcohol‐Fuelled Violence policies or other local factors.